Growing Students' Moral Reasoning Through Parenting Parenting in Elementary Schools: Menumbuhkan Penalaran Moral Siswa Melalui Pola Asuh Orang Tua di Sekolah Dasar - Pramesty Ayu Imelia; Supriyadi Supriyadi (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to describe students' moral reasoning and parenting applied by parents in growing students' moral reasoning at Leminggir State Elementary School. This research is a qualitative research with a case study research design. The subjects in this study were the fifth grade students of the Leminggir State Elementary School. Data collection was taken through interviews, observation, and documentation. The results of this study indicate that (1) The moral reasoning of fifth grade students at Leminggir State Elementary School shows at level II (Conventional Morality) namely in the first stage: Child orientation or a good person. (2) The parenting pattern of parents in growing children's moral reasoning is by fostering obedience to religious moral teachings that are accustomed to daily life with religious moral values ​​such as discipline, honesty, and not being arrogant that have been applied to have an impact on children's lives such as and children's words are more orderly, children can distinguish between good and bad even if only a few actions.